Whose Credit Line is it Anyway : An Update on Banks' Implicit Subsidies - Gudmundsson, Tryggvi (Washington, D.C. : International Monetary Fund, 2016)
The post-crisis financial sector framework reform remains incomplete. While capital and liquidity requirements have been strengthened, doubts remain over other aspects, including the fact that expectations of government support for systemically-important banks (SIBs) remain intact. In this paper, we use a jump diffusion option-pricing approach to provide estimates of implicit subsidies gained by these banks due to the expectation of protection to creditors provided by governments. While these subsidies have declined in the post-crisis era as volatility has declined and capital levels have increased, they remain non-trivial. Even conservative parameterizations of default and loss probabilities lead to macroeconomically significant figures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet